Analysis of toxic plant and mushroom poisoning in children - Gül, Evrim; Sarı, Mehmet Yusuf (My University, 2020)
Aim: The aim is to evaluate geographical, sociodemographic, laboratory, clinical features and follow-up and treatment outcomes ofchildren with toxic plant and mushroom poisoning.Material and Methods: From 2015 to 2017, cases aged between 1 month and 18 years and diagnosed with toxic plant and mushroompoisoning were retrospectively evaluated.Results: The mean age of the patients was 6.0±3.2 and the male/female ratio was 2.8. Mushrooms were the most common factorsfor poisoning (36.8%). The average time for application to the health facility was 2.4±1.9 hours. Poisoning was most commonly seenin summer (42.1%) and the most common complaint was vomiting. Most of the family members were primary school graduates.Treatment methods were activated charcoal (53%), activated charcoal and gastric lavage (26%), gastric lavage, activated charcoaland acetyl cysteine (11%) and acetyl cysteine (5%). One patient (5%) was applied followed up. Extracorporeal treatment was appliedto two patients who developed liver and renal failure during treatment and follow-up. During the laboratory comparisons before andafter hospitalization, white blood cell, creatinine kinase, aspartate aminotransferase and alanine aminotransferase levels were foundto be significant (p <0,05).Conclusion: In childhood age group, more informative, symptomatic and supportive treatments can lead to positive results in toxicplant and mushroom poisonings. Sometimes more aggressive treatment methods such as extracorporeal treatment may be needed.Close monitoring of laboratory parameters in mushroom and plant intoxication cases due to late manifestations has an importantrole in patient follow-up and treatment.
Keywords: Halk ve Çevre Sağlığı; Veterinerlik; Pediatri; Tıbbi Laboratuar Teknolojisi